Exploring the Efficacy of Constraint in Animal Models of Stroke: Meta-analysis and Systematic Review of the Current Evidence. (January 2013) - Janssen, Heidi; Speare, Sally; Spratt, Neil J.; Sena, Emily S.; Ada, Louise; Hannan, Anthony J.; McElduff, Patrick; Bernhardt, Julie
Background . Constraint-induced movement therapy (CIMT) is used to counteract learned nonuse observed following stroke in humans and has been shown to improve function. Variations of CIMT used in animal models of stroke have the potential to inform and improve our understanding of this intervention. Objective . To conduct a systematic review of studies investigating constraint in experimental stroke. The authors aimed to assess the quality and establish the efficacy of constraint on neurobehavior, cognitive function, infarct size, and stress and mortality and to determine the optimal dose or time to administration. Methods . Systematic review with meta-analysis was used. Data were analyzed using DerSimonian and Laird weighted-mean-difference random effects meta-analysis. Results . The quality scores of the 8 articles (15 studies) included were moderate (median 5/10; interquartile range, 4.8-6.0). There was a trend for animals with constraint to have worse neurobehavioral scores (−10% worse; 95% confidence interval [CI] = −20 to 0; P = .06). Infarct volumes were not significantly different between groups (−3% larger with constraint; 95% CI = −15 to 9; P = .63). Cognitive function was significantly better after constraint, although this estimate was based on only 28 animals from 2 studies. Insufficient data prevented analysis of the effect of constraint on stress and mortality. Conclusions . This meta-analysis showed no benefit of constraint on neurobehavioral scores, which is at odds with some human studies. Animal models may help us efficiently explore the biological basis of rehabilitation interventions; however, review of the data in this study raise uncertainty about its effectiveness in humans.